2017
DOI: 10.3390/s18010006
|View full text |Cite
|
Sign up to set email alerts
|

Screen-Printed Electrode Modified by Bismuth /Fe3O4 Nanoparticle/Ionic Liquid Composite Using Internal Standard Normalization for Accurate Determination of Cd(II) in Soil

Abstract: The quality and safety of agricultural products are threatened by heavy metal ions in soil, which can be absorbed by the crops, and then accumulated in the human body through the food chain. In this paper, we report a low-cost and easy-to-use screen-printed electrode (SPE) for cadmium ion (Cd(II)) detection based on differential pulse voltammetry (DPV), which decorated with ionic liquid (IL), magnetite nanoparticle (Fe3O4), and deposited a bismuth film (Bi). The characteristics of Bi/Fe3O4/ILSPE were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 31 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Chitosan (CHT) is a natural polymer with abundant primary amino and hydroxyl groups; it has excellent adhesion, hydrophilicity, doping feasibility, and chemical stability. A novel electrode was coated with a mixture of Fe 3 O 4 and CHT solution on an ionic liquid solid phase extraction, followed by a bismuth film deposited in situ; such electrode combined the advantages of Fe 3 O 4 , CHT, and ionic liquid screen-printed electrode (ILSPE), and accurately detected the content of Cd 2+ in soil samples thus reducing the contamination of cultivated rice [ 51 ].…”
Section: Nanotechnology-based Heavy Metal Analysis In Food and Watermentioning
confidence: 99%
“…Chitosan (CHT) is a natural polymer with abundant primary amino and hydroxyl groups; it has excellent adhesion, hydrophilicity, doping feasibility, and chemical stability. A novel electrode was coated with a mixture of Fe 3 O 4 and CHT solution on an ionic liquid solid phase extraction, followed by a bismuth film deposited in situ; such electrode combined the advantages of Fe 3 O 4 , CHT, and ionic liquid screen-printed electrode (ILSPE), and accurately detected the content of Cd 2+ in soil samples thus reducing the contamination of cultivated rice [ 51 ].…”
Section: Nanotechnology-based Heavy Metal Analysis In Food and Watermentioning
confidence: 99%
“…Bismuth film electrodes (Bi-modified) SPEs has been reported to offer a simple, portable, mass-produce and yet sensitive and with and multi-element detection capabilities of HM such as Cd 2+ and Pb 2+ . 56,57,134 Bastos-Arrieta et al 135 recently reported that the main factor to enhance SPE's electrocatalytic performance is the shape of the nanoparticles, rather than the mere incorporation of them, when detecting Cd 2+ or Pb 2+ with Ag-NP SPEs. Barton et al 27 elegantly reviewed the use of Au-coated SPEs to detect HM, showing the determination of Pb 2+ , Cd 2+ , Hg 2+ , As 2+ , Cu 2+ and Sb 2+ in a variety of modifications such as Au bulkmodified inks, Au-coated, Au-sputters and nano-deposited, towards matrixes such as ground-, 136 river-, [137][138][139] rain-, 140 waste-, 138 sea-waters [141][142][143] and soil extracts.…”
Section: Electrode Modificationsmentioning
confidence: 99%
“…With electrochemistry development, bismuth-modified electrodes have been used widely in the electroanalysis of an electrochemical sensor because of its low toxicity [158][159][160][161][162]. An enhanced bismuth film enclosed single-walled carbon nanotube (Bi/SWNT) composite was used effectively to fabricate an electrochemical sensor for the highly sensitive detection of trace chromium (IV) in actual samples with a fairly low 0.036 μM detection limit [163].…”
Section: Bismuth As Electrocatalyst and Fuel Cell Catalystmentioning
confidence: 99%